(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Oxidative stress is a common point in neurodegenerative diseases, widely connected with mitochondrial dysfunction. In this study, we screened seven natural products from Streptomyces sources against hydrogen peroxide insult in primary cortical neurons, an oxidative stress in vitro model. We showed the ability of these compounds to inhibit neuronal cytotoxicity and to reduce ROS release after 12 h treatment. Among the tested compounds, the quinone anhydroexfoliamycin and the red pyrrole-type pigment undecylprodigiosin stand out. These two compounds displayed the most complete protection against oxidative stress with mitochondrial function improvement, ROS production inhibition, and increase of antioxidant enzyme levels, glutathione and catalase. Further investigations confirmed that anhydroexfoliamycin acts over the Nrf2-ARE pathway, as a Nrf2 nuclear translocation inductor, and is able to strongly inhibit the effect of the mitochondrial uncoupler FCCP over cytosolic Ca2+, pointing to mitochondria as a cellular target for this molecule. In addition, both compounds were able to reduce caspase-3 activity induced by the apoptotic enhancer staurosporine, but undecylprodigiosin failed to inhibit FCCP effects and it did not act over the Nrf2 pathway as was the case for anhydroexfoliamycin. These results show that Streptomyces metabolites could be useful for the development of new drugs for prevention of neurodegenerative disorders such as Parkinson’s and Alzheimer’s diseases and cerebral ischemia.